PENGARUH ASAM HUMAT SEBAGAI PELENGKAP PUPUK PADA TANAMAN JAGUNG TERHADAP EFISIENSI PEMUPUKAN DI LAHAN KERING KEC. BAYAN KAB. LOMBOK UTARA NTB (THE INFLUENCE OF HUMIC ACID AS FERTILIZER SUPPLEMENT ON MAIZE PLANT TO FERTILIZING EFFICIENCY IN UNIRRIGATED LAN - Hermanto, Dhoni; Tri Dharmayani, Ni Komang; Kurnianingsih, Rina; Kamali, Siti Raudhatul (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2012)
A study of the influence of humic acid as fertilizer supplement on maize plant to fertilizing efficiency in unirrigated land of Kec. Bayan Kab. Lombok Utara NTB was conducted. Agricultural land of Kec. Bayan has the physical properties of sandy texture, loose structure and reddish brown with neutral acidity (pH 6.97 at a depth of 0-20 cm and a pH of 6.8 at a depth of 21-40 cm). In addition, it has low nutrient level of soil (Corganic, N, P, K) at depths 0-20 cm and 21-40 cm respectively are 0.912% and 1.150%; 0.064% and 0.074%; 0.001% and 0.005 %; 0.290% and 0.310%. Application of humic acid as fertilizers supplement improved the availability of major and micronutrients and enhanced their uptake. The highest availability and uptake of N, P and K was found in addition of humic acid @ 20 kg ha-1 along with 100% recommended dose of fertilizers. Application of humic acid in soil showed increasing of plant growth (plant height, weight and nutritional value of corn). Fertilized N, P and K without humic acid was provided of fertilizing efficiency below 50 %. The most efficient dose for humic acid fertilizer is 20 kg ha-1 along with 150 kg ha-1 of urea, 200 kg ha-1 of SP36 and 50 kg ha-1 of KCl.